The effect of feeding fresh swine manure, poultry waste, urea, molasses and bakery by-products ensiled for lambs - Fernando MartÃnez San Pedro; Ignacio A. DomÃnguez Vara; JosÃ© Luis BÃ³rquez; Manuel Gonzalez-Ronquillo (International Journal of Recycling of Organic Waste in Agriculture)
Introduction The use of by-products such as swine manure (SM), poultry waste (PW), urea (U), molasses (M) and bakery by-product (BB) is an alternative method for lamb feeding. The objective of the present study was to determine the chemical composition, dry matter intake and digestibility in growing lambs using ensiled PW combined with BB (PWBB), SM with BB (SMBB), SM with M (SMM) and U with M (UM) in their diets. Methods Four silagesâPWBB, SMBB, SMM and UMâ were prepared, the chemical composition of the silages was determined (n = 3), silages and concentrate ratio (60:40) as fresh matter were given to growing lambs over 21 days as total period, and the collection of samples to determine intake and digestibility was carried out for the last 7 days, in a 4 9 4 Latin square design, with a significance level P.05. Results The organic matter (OM) was lower (P.05) in silage with SMM (886 g/kg), and crude protein increased with UM (206 g/kg) followed by PWBB (170 g/ kg). DM, OM, NDF and ADF intake was higher (P.05) in UM diets compared with the rest of the treatments; ADF digestibility was lower (P.05) for SMM (389 g/kg) than UM (417 g/kg) diets. N intake was higher (P.05) in UM (51.3 g N/day) diets than the rest of the treatments (39.9 ± 1.3 g N/day). Conclusions The use of PWBB, SM combined with BB or M is an alternative method for lamb feeding, provided that a proper formulation supplies the nutrient requirements of crude protein and diminish the N excretion compared with UM diet.